Alces alces - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Alces alces (Linnaeus 1758) [Cervus] alces Linnaeus 1758, Syst. Nat., 10th ed., Vol. 1: 66. Type Locality: "Habitat in boroealibus Europae, Asiaeque Populetis"; identified as Sweden by Thomas (1911 a :151). Vernacular Names: Eurasian Elk. Subspecies:: Subspecies Alces alces subsp. alces Linnaeus 1758 Subspecies Alces alces subsp. caucasicus Vereshchagin 1955 Distribution: N Eurasia from Scandinavia, Poland, N Austria, and S Czech Republic (vagrant in Croatia, Hungary, and Romania), east to the Yenisei River (Siberia) and south to Ukraine, N Kazakhstan, N China (N Sinkiang), and possibly adjacent parts of Mongolia; extinct in Caucasus region since 19 th century. Conservation: IUCN – Lower Risk (lc). Discussion: Differs from A. americanus in karyotype, body dimensions and proportions, form of premaxilla, colouration, and structure and dimensions of antlers (Boyeskorov, 1999; Geist, 1998). Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Artiodactyla, pp. 637-722 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 653, DOI: 10.5281/zenodo.7316519